PlasmidMaker is a versatile, automated, and high throughput end-to-end platform for plasmid construction - Behnam Enghiad; Pu Xue; Nilmani Singh; Aashutosh Girish Boob; Chengyou Shi; Vassily Andrew Petrov; Roy Liu; Siddhartha Suryanarayana Peri; Stephan Thomas Lane; Emily Danielle Gaither; Huimin Zhao (Nature Communications, 2022)
Despite their broad utility, design and construction of plasmids remains laborious and time-consuming. Here the authors report a robust, versatile, and automated end-to-end platform that enables scarless construction of virtually any plasmid.